Comparing adsorption of an electron-rich triphenylene derivative: metallic vs graphitic surfaces - Rie, Joris de la; Wang, Qiankun; Enache, Mihaela; Kivala, Milan; Stöhr, Meike (The journal of physical chemistry. C, Energy, materials, and catalysis, 2024)
Crucial to the performance of devices based on organic molecules is an understanding of how the substrate-molecule interface influences both structural and electronic properties of the molecular layers. Within this context we studied the self-assembly of an alkoxy-triphenylene derived electron donor (HAT) in the monolayer regime on graphene/Ni(111). The molecules assembled into a close-packed hexagonal network commensurate with the graphene layer. Despite the commensurate structure, the HAT molecules only had a weak, physisorptive interaction with the substrate as pointed out by the photoelectron spectroscopy data. We discuss these findings in view of our recent reports for HAT adsorbed on Ag(111) and graphene/Ir(111). For all three substrates HAT adopts a similar close-packed hexagonal structure commensurate with the substrate while being physisorbed. The ionization potential is equal for all three substrates, supporting weak molecule-substrate interactions. These findings are remarkable, as commensurate overlayers usually only form at strongly interacting interfaces. We discuss potential reasons for this particular behavior of HAT which clearly sets itself apart from most studied molecule-substrate systems. In particular, these are the relatively weak but flexible intermolecular interactions, the molecular symmetry matching that of the substrate, and the comparatively weak but directional molecule-substrate interactions.
Online veröffentlicht: 19. Juni 2024
Gesehen am 18.11.2024